Weak effects of habitat type on susceptibility to invasive freshwater species: an Italian case study. Issue 6 (7th March 2014) - Boggero, Angela; Basset, Alberto; Austoni, Martina; Barbone, Enrico; Bartolozzi, Luca; Bertani, Isabella; Campanaro, Alessandro; Cattaneo, Antonella; Cianferoni, Fabio; Corriero, Giuseppe; Dörr, Ambrosius Martin; Elia, A. Concetta; et al.
ABSTRACT Introduction of alien species is one of the major threats to aquatic biota and knowledge of the major correlates of their occurrence is pivotal in planning reliable conservation strategies. To understand whether specific freshwater habitats are more likely to be invaded than others, a dataset on the occurrence of 1604 species in 54 taxonomic groups from 181 sites across the Italian peninsula was gathered. The EUNIS habitat classification was used, selecting for the study's seven habitat types at the second EUNIS level, including lentic (EUNIS C1; 64 sites), lotic (EUNIS C2; 99 sites) and highly artificial (EUNIS J5; 18 sites) habitats. The aim of the study was to test whether the overall number of alien species and the proportion of alien species for each taxonomic group differed between habitat types and could be explained by environmental, human‐mediated, or climatic factors. Using generalized linear mixed effect models to account for potential confounding factors, only average air temperature of the site was a significant positive predictor of the occurrence of alien species, regardless of habitat type, species richness, and other climatic variables. A direct effect of temperature could be excluded given the origin of alien species, mostly from colder areas than Italy. Thus, an indirect effect could be hypothesized at the Italian latitudes, with warmer areas potentially more likely to be visited by tourists than colder areas. If this hypothesis is confirmed, the results of the analyses call for a compromise between the maintenance of recreational activities in the wild and the preservation of a natural environment to prevent the arrival and spread of alien species. On the other hand, no further recommendations can be implemented regarding habitat susceptibility to alien species. Copyright © 2014 John Wiley & Sons, Ltd.